2009
DOI: 10.1007/s11325-009-0306-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CPAP treatment on cardiac biomarkers and pro-BNP in obstructive sleep apnea syndrome

Abstract: Obstructive sleep apnea syndrome does not induce myocardial damage enough to increase serum pro-BNP, CK, CK-MB, troponin I, and AST levels. Markers sensitive to ischemia could be preferred to evaluate effect of obstructive sleep apnea syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…At 3, 6, and 12 months of follow-up, there was no significant change in NT-pro-BNP levels compared with baseline. In agreement with these data, Cifçi et al (20) did not detect any significant difference in the levels of pro-BNP after 6 months of CPAP therapy. Only patients with moderate or severe OSAHS were included and none had congestive heart failure.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…At 3, 6, and 12 months of follow-up, there was no significant change in NT-pro-BNP levels compared with baseline. In agreement with these data, Cifçi et al (20) did not detect any significant difference in the levels of pro-BNP after 6 months of CPAP therapy. Only patients with moderate or severe OSAHS were included and none had congestive heart failure.…”
Section: Discussionsupporting
confidence: 72%
“…In multiple regression analysis, NT-pro-BNP was significantly correlated with left ventricular ejection fraction, creatinine clearance, and the presence of arterial hypertension but not with AHI. Likewise, Cifçi et al (20) evaluated 33 patients with OSAHS and did not find statistically significant increases in the levels of serum BNP. Consequently, they concluded that OSAHS does not induce enough myocardial damage to increase serum BNP levels.…”
Section: Discussionmentioning
confidence: 95%
“…Contrary to other studies, however, they showed that there was no change in NT-proBNP level after CPAP treatment (10,25). Similarly, Çifçi et al failed to establish a correlation between OSAS severity and plasma NT-proBNP levels, and reported that NT-proBNP levels were not altered with CPAP treatment (11). In the light of these few studies with conflicting results, it is still unclear what kind of correlation exists between CPAP treatment and serum BNP levels.…”
Section: Discussionmentioning
confidence: 90%
“…The literature contains various studies evaluating NT-proBNP levels before and after CPAP treatment, but this issue has conflicting results (9)(10)(11). Ischemia-modified albumin (IMA) is formed as a result of the normal human albumin N-terminal region undergoing alteration during ischemia (12).…”
Section: Introductionmentioning
confidence: 99%
“…Cifci et al (30) also concluded that OSAS did not induce myocardial damage enough to increase CK, CK-MB and troponin I. Some reports (11,31) showed that patients with SAHS could have more collateral vessels, which may lead to myocardial preconditioning.…”
Section: Discussionmentioning
confidence: 99%